Recent developments in the assessment of the immune response to malaria, especially as related to vaccination: Lethal Plasmodium yoelii malaria: the role of macrophages in normal and immunized mice - Playfair, J. H. L. (1979)
Mice were injected with silica or Corynebacterium parvum, which, respectively, inhibit and stimulate macrophages in vivo, in an attempt to study the role of macrophages in lethal Plasmodium yoelii infection and in mice protected by immunization. In the normal infection, macrophages were able to control parasitaemia for up to 1 week, whereas in immunized mice they appeared to inhibit the sterilizing immune response. A model is proposed in which this dual role of activated macrophages may account for the chronic non-sterilizing course of natural malaria infections.